Clinical Pharmacy Activities in Swiss Hospitals: How Have They Evolved from 2013 to 2017? - Helene Studer; Fabienne Boeni; Markus Messerli; Kurt E. Hersberger; Markus L. Lampert (MDPI AG, 2020)
The role of pharmacists is changing; in many countries, pharmacists have acquired new competencies. A survey conducted in 2013 mapped the clinical pharmacy services in Swiss hospitals by quantifying full-time equivalents (FTE) and depicting clinical pharmacy activities. The aim of this survey was to update these results and analyze the development in Swiss hospitals. An online questionnaire was sent to chief hospital pharmacists (n = 60). The questionnaire was developed based on the previous survey and on a literature search. The survey took place from June to September 2017. In the survey, 44 hospital pharmacies participated (return rate 73%). They counted 265.8 FTE for pharmacists; 31 offered clinical pharmacy services. Hospitals participating in both surveys (n = 32) showed a significant increase in FTE for hospital (+24.5%) and clinical (+62.7%) pharmacists. The number of training positions available for the certificate of proficiency in “clinical pharmacy” has increased by 5.5. Patient-related services are less commonly implemented in comparison to treatment and process-related services. In conclusion, the increase in FTE of clinical pharmacists was more pronounced than of hospital pharmacists in general. For further development and broader implementation of clinical pharmacy services, however, hospital pharmacies should increase the number of training positions and should direct more activities towards patient-related services.